Pengaruh Pengalaman Auditor Dan Etika Auditor Terhadap Kualitas Audit Pada Kantor Akuntansi Publik (KAP) Surabaya - Aquelis Alves Barreto (Jurnal Mutiara Ilmu Akuntansi, 2023)
Every company has an audit with the aim of checking whether the financial statements that have been made are presented in accordance with the reporting standards. The importance of the role of the auditor in the audit process requires the auditor to be able to work optimally. There are several factors that influence the auditor in conducting an audit, one of which is the auditor's experience and auditor ethics. The purposes of conducting this research are: 1) To find out whether Auditor Experience has a partial effect on Audit Quality, 2) To find out whether auditor ethics have a partial effect on Audit Quality, and 3 To find out whether Auditor Experience and auditor ethics have a simultaneous effect on Audit Quality. This research uses a quantitative approach. This research is also included in the causal quantitative research conducted at KAP in Surabaya. The population in this study were auditors who worked at the Arsono and Jimmy Public Accounting Firms, Teramihardja, Pradhono, Chandra and Danny Wibowo KAPs, with a total sample of 30 people. Data comes from primary data sources obtained from distributing questionnaires. Data analysis uses multiple linear regression analysis. The results show that: 1) Auditor experience influences Audit Quality, 2) Auditor Ethics influences Audit Quality, and 3) Auditor Experience and auditor ethics simultaneously influence Audit Quality. Therefore, it is hoped that the Public Accounting Firm (KAP) in Surabaya can improve Auditor Experience and Auditor Ethics to improve audit quality..